Kajian Pemanfaatan Jurnal Online Pada Perpustakaan Universitas Riau Pekanbaru - Thamrin Hasan (Perpustakaan Universitas Riau, 2013)
Journal Online is one of the best solutions in obtaining the literature. It is closely related to the advancement of information technology evolves. Along with advances in information and communication technologies the distance, time and space to be virtually no limit. The phenomenon that occurs in many college libraries in the use of online journals are not much different. In the library of the University of Riau alone indicated was rarely used. Thus, the aim of this study was to determine the extent to which the use of online journals by students at the University of Riau. This research is a descriptive, population as respondents were 140 students with techniques for sampling conducted accidental. The results showed that: 1) the frequency of use of the online journal was more dominant at a frequency of 1 to 2 times a week (67.86%), 2) the timeframe used most predominantly between 1 to 2 hours (61.43%), 3) the level of students' ability in alkaline Boolean operators AND, OR, NOT quite understand the category (63.57%), 4) the action is the dominant search print / print out (57.86%), 5) the access point information retrieval through the dominant subject / keywords (69.29%), 6) difficulty of using a foreign language / English quite high (45.71%), 7) where access journals do in the library (90.71%), 8) The purpose of the journal for purposes of study (60.71%) 9) information needs can be met by either (78.57%), 10) need the help of librarians (64.29%), 11) the role of the librarian is very important (84.29%), 12) difficulties when search for information online journals (67.86%).